STUDY OF SOME PHYSICAL AND MECHANICAL CHARACTERISTICS OF PAULOWNIA TOMENTOSA S. WOOD PLANTED IN NORTHERN IRAQ - O. I. Ahmed; M. M. Ibrahim; O. A. Hasan; I. H. Zainulabdeen (مجلة الأنبار للعلوم الزراعية)
This study was conducted at the College of Agriculture, University of Kirkuk to determine the physical and mechanical characteristics of the wood of the Paulownia tomentosa S. tree grown in northern Iraq as an input species for wood production. Eight-year-old trees were selected as this species is characterized by its rapid cutting cycles. Its dry density of 0.2968 g/cm3 and basic density of 0.2745 g/cm3 were almost low values, negatively affecting their mechanical and physical properties. The ratios of volumetric shrinkage, volumetric swelling, fiber saturation point, immersion moisture content, and maximum moisture content stood at 7.6440, 8.2783, 27.8775, 156.0845 and 298.9300 %, respectively. This is considered as having good dimensional stability which reduces the risk of cracking and warping upon drying. The percentage of wood in the cell wall reached 19.79% while its porosity was 80.21%, consistent with other findings on the physical attributes of this tree species. Mechanical strength values in terms of MOE, MOR, tension parallel to the grain, hardness, and compression parallel to the grain were 4002, 57.1285, 36.03, 15.75, and 31.025 N/mm2, respectively. Based on these values this wood is suitable for low-load purposes such as insulation partitions in construction, packaging materials, furniture, and agricultural supplies